Proteinuria and Hyperglycemia Induce Endoplasmic Reticulum Stress - Lindenmeyer, Maja T. (American Society of Nephrology, 2008)
The endoplasmic reticulum (ER) is an important site for protein folding and becomes “stressed” when its capacity to fold proteins is overwhelmed. In response, “unfolded protein response” (UPR) genes are induced, increasing the capacity to fold proteins; if the response is insufficient, then apoptosis ensues. For investigation of whether proteinuria and hyperglycemia induce ER stress in renal epithelial cells, microarray data from biopsies of established diabetic nephropathy (DN) were analyzed. Expression of UPR genes was significantly different in these biopsies than in control kidneys or biopsies of patients with mild DN, suggesting an association between the degree of DN and UPR gene expression. Expression of the transcription factor XBP1 and the ER chaperones HSPA5 and HYOU1 were increased, but the proapoptotic gene DDIT3 was unchanged. These findings were replicated in an independent cohort of patients with established DN by real-time reverse transcriptase–PCR. Immunofluorescence of renal biopsies from patients with DN confirmed the upregulation for HSPA5 and HYOU1 proteins in tubular epithelia. In biopsies of minimal-change disease, the mRNA levels of some ER stress molecules were also induced, but protein expression of HSPA5 and HYOU1 remained significantly lower than that observed in DN. Exposure of renal tubular epithelial cells to albumin and high glucose in vitro enhanced expression of genes involved in ER stress. These observations suggest that in proteinuric diseases, tubular epithelial cells undergo ER stress, which induces an adaptive, protective UPR. Although this may protect the cells from ER stress, persistence of hyperglycemia and proteinuria may eventually lead to apoptosis.